Environmental law research groups in Spanish public universities: Characterization and presence in social networks - Mercadal Cuesta, David; Siso Calvo, Brenda (Advanced Notes in Information Science, 2024)
It is imperative that research in environmental law be conducted in order to facilitate scientific progress and the protection of the planet. University research groups are the fundamental units for the creation and generation of scientific knowledge. The dissemination of research processes and results is crucial for university research groups, as it facilitates access to information and enhances their reputation, thereby expanding their reach. This study’s primary objective is to characterize environmental law research groups from Spanish public universities based on three key variables: size, gender, and lines of research. Additionally, it aims to assess the presence and activity of these groups on social networks “X” and “ResearchGate.” The principal findings indicate that the majority of these groups are relatively small, comprising between three and 11 members. There is a moderate degree of gender equality within these groups, and their lines of research are broad and interdisciplinary in nature. Furthermore, it is evident that the visibility of these groups on social networks, particularly on X and ResearchGate, remains limited. Despite efforts to maintain an active digital presence, there is a clear need for continued work in this area to achieve the desired outcomes related to the dissemination of research activity and scientific production. The integration of social media into this process is a crucial element.